The effect of intervention using audio-visual media and demonstration on changes in feeding behavior and nutritional status of children under five - Eny Retna Ambarwati; Reni Tri Lestari; Ivanna Beru Brahmana; Widyastuti Andriyani; Murgi Handari; Istichomah Istichomah; Agnes Erida Wijayanti; Riadinata Riadinata; Fika Pratiwi (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Childhood malnutrition remains a significant public health concern in Indonesia, with maternal knowledge and feeding practices playing a crucial role in determining children's nutritional outcomes.Purpose: to evaluate the effectiveness of a health promotion intervention combining audio-visual media and practical demonstrations in improving maternal feeding practices and the nutritional status of children under five. Method: A quasi-experimental one-group pretest–posttest design was conducted among 42 mothers and their under-five children at Tapak Dara Integrated Health Post, Bantul, Yogyakarta. Maternal knowledge and feeding practices were assessed using structured questionnaires, while children's nutritional status was measured through weight-for-age Z-scores. The intervention included educational video sessions followed by hands-on demonstrations. Data were analyzed using paired t-tests or Wilcoxon signed-rank tests and chi-square tests.Results: Most participants were of reproductive age (54.8%), had secondary education (59.5%), and were employed (76.2%). Post-intervention findings showed significant increases in knowledge scores (17.2 to 18.9; p<0.001) and practice scores (18.3 to 19.4; p<0.001). The proportion of children with good nutritional status improved from 61.9% to 73.8%. Significant associations were found between knowledge and feeding practices (p=0.012) and between feeding practices and nutritional status (p=0.008). Conclusion: Audio-visual and demonstration-based interventions effectively enhance maternal feeding practices and child nutritional status.